Genomic sequence derived simple sequence repeat markers: case study with Medicago spp - Mahalakshmi, V.; Aparana, P.; Ramadevi, S.; Ortíz, R. (Elsevier, 2002)
Simple sequence repeats (SSR) or micro-satellites are becoming standard DNA markers for plant genome analysis and are being used as markers in marker assisted breeding. De novo generation of micro-satellite markers through laboratory-based screening of SSR-enriched genomic libraries is highly time consuming and expensive. An alternative is to screen the public databases of related model species where abundant sequence data is already available. All the genomic sequences of Medicago from the public domain database were searched and analysed of di, tri, and tetra nucleotide repeats. Of the total of about 156,000 sequences which were searched, 7325 sequences were found to contain repeat motif and may yield SSR which will yield product sizes of around 200 bp. Of these the most abundantly found repeats were the tri-nucleotide (5210) group. Except for a very small proportion (436), these link to the gene annotation database at TIGR (http://www.tigr.org).